2017
DOI: 10.1017/s0007114517002884
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal maternal high-fat diet induces early obesity and sex-specific alterations of the endocannabinoid system in white and brown adipose tissue of weanling rat offspring

Abstract: Perinatal maternal high-fat (HF) diet programmes offspring obesity. Obesity is associated with overactivation of the endocannabinoid system (ECS) in adult subjects, but the role of the ECS in the developmental origins of obesity is mostly unknown. The ECS consists of endocannabinoids, cannabinoid receptors (cannabinoid type-1 receptor (CB1) and cannabinoid type-2 receptor (CB2)) and metabolising enzymes. We hypothesised that perinatal maternal HF diet would alter the ECS in a sex-dependent manner in white and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 115 publications
(156 reference statements)
1
24
1
Order By: Relevance
“…Thus, we cannot rule out that changes in expression or function of the eCB system in pancreas and small intestinal epithelium occur in pups born from WD mothers at earlier time points and is transient, or at later time points from our analysis of eCB system expression and feeding behavior in pups (i.e., 10 weeks after weaning). Indeed, other groups reported sex-specific changes in eCB system expression in white and brown adipose depots in rat pups born from mothers maintained on a high-fat diet versus standard; however, in contrast to our experiments, their analysis occurred immediately after weaning [ 15 ]. Similarly, Ramirez-Lopez and colleagues reported reductions at birth in levels of the eCBs, AEA and 2-AG, in the hypothalamus of male rats born from mothers maintained on a high-calorie test diet versus standard chow during the pregestational and gestational periods [ 54 ].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Thus, we cannot rule out that changes in expression or function of the eCB system in pancreas and small intestinal epithelium occur in pups born from WD mothers at earlier time points and is transient, or at later time points from our analysis of eCB system expression and feeding behavior in pups (i.e., 10 weeks after weaning). Indeed, other groups reported sex-specific changes in eCB system expression in white and brown adipose depots in rat pups born from mothers maintained on a high-fat diet versus standard; however, in contrast to our experiments, their analysis occurred immediately after weaning [ 15 ]. Similarly, Ramirez-Lopez and colleagues reported reductions at birth in levels of the eCBs, AEA and 2-AG, in the hypothalamus of male rats born from mothers maintained on a high-calorie test diet versus standard chow during the pregestational and gestational periods [ 54 ].…”
Section: Discussionmentioning
confidence: 58%
“…The authors then analyzed expression of eCB system components in brain, liver, and adipose tissue in these rats at nineteen weeks postnatal and found a variety of sex-specific changes in expression of mRNA for several components of the eCB system (see for details [ 16 ]). Collectively, these studies reveal possible changes in eCB system function or expression in several organs immediately after birth [ 54 ] or weaning [ 15 ], and at much later timepoints (i.e., nineteen weeks postnatal [ 16 ]) in offspring born from dams consuming high-energy diets. Furthermore, under our conditions, similar expression and function of the eCB system between groups in the upper small intestinal epithelium–particularly given its critical role in feeding behavior [ 45 47 , 49 ]–may underlie a lack of change in feeding patterns or palatable food preferences observed between mice born from WD or SD dams at the time point analyzed in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, very little is known regarding the direct ECS regulation by sex steroids, even in control rats, mice or humans 24 . In our previous studies 7 , 8 , we characterized that the ECS is differentially regulated in male and female HF offspring in other tissues, such as white and brown adipose tissue and hypothalamus. Interestingly, ECS changes can occur even before the major physiological alterations in sex hormone levels during puberty, since we observed that maternal HFD induces ECS sex-specific changes already at birth 8 and also at weaning 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Protein content of ECS targets and 4-HNE was determined by western blotting in liver homogenate as previously described with some adaptations 7 , 8 . Each sample was obtained from a different rat from a different litter (n = 7).…”
Section: Methodsmentioning
confidence: 99%
“…We ( Zambrano et al, 2010 , 2016 ; Rodriguez et al, 2012 ; Santos et al, 2015 ; Vega et al, 2015 ; Bautista et al, 2017 ) and others ( Sen and Simmons, 2010 ; Elshenawy and Simmons, 2016 ; Lecoutre et al, 2016 ; Wankhade et al, 2016 ) have studied the rat as an experimental animal model of the metabolic consequences of maternal (F0) obesity (MO) in offspring (F1). In addition, several studies have shown differential responses in male and female F1 from obese mothers ( Vega et al, 2015 ; Almeida et al, 2017 ; Carrillo et al, 2017 ). Variable physiological conditions can profoundly either reduce or increase adipose tissue lipid storage capacity by up to 15-fold ( Berry et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%